Does lung function predict the risk of disability pension? An 11-year register-based follow-up study - Irmeli Lindström; Paula Pallasaho; Jouko Remes; Tuula Vasankari; Markku Heliövaara (BMC, 2020)
Abstract Background Spirometry is widely used in medical surveillance in occupational health and as a diagnostic test for obstructive and restrictive lung disease. We evaluated the effect of spirometry parameters on the risk of all-cause disability pension in a follow-up study of an occupationally active general population-based cohort. Methods We measured the pulmonary function of 3386 currently working participants of the Health 2000 Survey in the clinical phase at baseline using spirometry. We obtained the retirement events of the cohort from the nationwide register for 2000-2011. Cox proportional hazards models were used to determine disability pensions. Results At baseline, we identified 111 (3.3%) participants with obstructive spirometry, 95 (2.8%) with restrictive spirometry, and 3180 controls without restriction or obstruction. The age, sex, educational level, body-mass index, co-morbidities (1 or ≥ 2), and the smoking-adjusted hazard ratio of disability pension was 1.07 (95% confidence interval, CI 0.64-1.78) for those with obstructive spirometry, and 1.44 (95% CI 0.89-2.32) for those with restrictive spirometry. As continuous variables, and divided into quartiles, the risk of the lowest quartile of forced ventilation capacity (FVC)% of predicted was 1.49 (95%CI 1.10-2.01) and forced expiratory volume in one second (FEV1)% of predicted 1.66 (95%CI: 1.23-2.24) in comparison to the highest quartile in the adjusted models. Conclusions Obstructive or restrictive spirometry did not predict disability pension when dichotomized classified variables (normal compared to abnormal) were used. As continuous variables and when divided into quartiles, lower lung volumes showed an increase in the risk of disability pension. Physicians should take this into account when they use spirometry as a prognostic factor of work disability.